Autobiography in the novel "Master of the ship" byYu Yanovsky (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article investigates autobiographical and autothematical novel “The Master of the ship”. Biographical facts allow deeper to reveal specific artistic skill of theartist, presenting the creative process as a means of self-expression writer.
Keywords: autobiographical; prototype; process art; artist; art